Development of instant bringhe - Tasarra, Christy G.; Azanza, Ma. Patricia V. (2000.)
ABSTRACT A formulation for instant bringhe was developed in this study, as part of the research project of UP-PhilRice entitled "Rice and Rice-Based Disaster Foods". This study was divided into 5 phases: selection of the most acceptable formulation of bringhe, standardization of the selected formulation, preparation of instant bringhe, quality assessment of instant bringhe, and cost analysis of the product. A base recipe for bringhe was developed from published Filipino recipes by Negado (1954), Gonzales(1993), Ramos and Reyes (1981), Silverio(1984) and Virmani (1991). The base recipe consisted of ingredients, which were common in all published recipes. Variation in the base recipe was incorporated by using 3 types of food colorants, namely, turmeric, kasubha and curry powder. Descriptive and Acceptability Tests showed that the recipe prepared with curry powder obtained the highest overall acceptability and was, therefore, selected. Modification of the selected recipe was done to improve its color and cohesiveness. The color of selected recipe was modified by adding turmeric, which was 30% of the curry powder. The cohesiveness was improved by addition of high amylose rice, IR42 variety, at a ratio of 2:1 (wt:wt) with low amylose rice, Malagkit Sungsong variety. The rice and vegetable components of the instant product were dried separately. Malagkit Sungsong was hydrated in 0.5% calcium chloride solution for 30 min; gelatinized with steam under pressure at 121.5°C for 6 min; and dehydrated at 55°C in an air convective dryer for 1.5 h. The IR 42 rice, on the other hand, was hydrated in a 1% solution of calcium chloride and sodium citrate. (50:50) at 50°C for 15 min; gelatinized with steam under pressure at 121.5°C for 4 min; and dehydrated in an air convective dryer at 50°-60°C for 1.5h. Before drying, the vegetables were washed, peeled/sliced and steam-blanched for 4-6 min. For carrots, additional treatment with 2.5% cornstarch solution was employed by quickly dipping the blanched carrots into the solution at 80°C. Dehydration of vegetables was carried out in an air convective dryer initially at 93°C for carrots and 82°C for green peas. This was effect rapid reduction of moisture content. The subsequent drying temperature for carrots was 65°C and 71°C for green peas. The meat components were substituted by TVP. The instant bringhe mix was prepared by compounding coconut milk powder, minced onion, minced garlic, curry powder, turmeric, pepper, salt, chicken fat flavor, chichen flavorings chicken concentrate, fish flavor blend and smoke flavor blend. The rehydrated instant bringhe was evaluated by 50 panelists using Descriptive and Acceptability Tests against the conventionally cooked bringhe. The rehydrated instant bringhe was described as having slightly rich in terms of creaminess. The instant product was also described as moderately bright and colorful, with yellow rice base color, firm but springy rice kernels, which were sticky with loose aggregates and as having firm but tender meat and vegetable components. The rehydrated instant product was found by panelists more acceptable than the conventionally cooked product. The overall acceptability of the rehydrated instant product was like moderately and was significantly different from the liked slightly conventionally prepared product at 5% level of significance. The pH values of the compounded and rehydrated instant product samples were 6.05 and 6.01, respectively. The Aw values were 0.45 and 0.98, respectively. The TPC of the compounded and rehydrated product were 〖10〗^5 and <〖10〗^2 cfu/g, respectively. The YMC were both <〖10〗^2. Cost analysis of the developed instant product showed that the estimated cost was P33.04 per 88 g serving portion (dry weight). The results of this study can be used in the production of instant bringhe for commercial use. Improvement of the method of dehydration of the vegetable components was recommended for the improvement of the instant product. Further studies, such as selection of proper packaging material and storage study of the instant product, were also recommended.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Cookery (Rice); Bringhe